Understanding Consumer Perception and Behavior Toward Biodegradable Plastic Products Based on the MOA Model - Baek, Nayeon; Lee, Hyemi (Asia Marketing Journal (Online), 2025)
This study investigated the factors influencing consumers' switching intentions to biodegradable plastic products. Applying a modified Motivation-Opportunity-Ability (MOA) framework, we analyzed the impact of factors such as environmental concern, novelty seeking, negative attitude, perceived consumer effectiveness, green consumer availability, and environmental knowledge on switching intention, while also examining the moderating effect of perceived greenwashing. Results showed that environmental concern, perceived consumer effectiveness, and negative attitude from the motivation dimension, and environmental knowledge from the ability dimension, had significant effects on switching intentions. Furthermore, it was found that the level of perceived greenwashing moderated the effects of environmental concern, perceived consumer effectiveness, and environmental knowledge on switching intentions. This study is significant for its focus on consumer perceptions and behavioral intentions towards biodegradable plastics as eco-friendly products, although there is room for debate about its actual environmental effectiveness. Based on the findings, we present practical implications that include the importance of consumer education, the need for companies to provide transparent information, and policy considerations to strengthen consumer sovereignty.